$ y= \frac{(2x+3)(4x-5) }{(1+x^2)(1+e^x)} $
วิธีทำ
\begin{align} & \cssId{Step1}{ take \quad \ln \quad จะได้ \quad \ln y= \ln (2x+3) + \ln (4x-5) - \ln(1+x^2) - \ln (1+e^x) } \\ &\cssId{Step2}{ดังนั้น \quad \frac{1}{y} \frac{dy}{dx} = \frac{1}{2x+3} 2 + \frac{1}{4x-5} 4 - \frac{1}{1+x^2} 2x - \frac{1}{1+e^x} e^x } \\ &\cssId{Step3}{ ดังนั้น \quad \frac{dy}{dx} = y ( \frac{2}{2x+3} + \frac{4}{4x-5} - \frac{2x}{1+x^2} - \frac{e^x}{1+e^x} ) } \\ &\cssId{Step4}{ = \frac{(2x+3)(4x-5) }{(1+x^2)(1+e^x)} ( \frac{2}{2x+3} + \frac{4}{4x-5} - \frac{2x}{1+x^2} - \frac{e^x}{1+e^x} ) } \\ \end{align}